CiCi [compact disc] - Ciara, 1985- (Beauty Marks Entertainment, 2025)
Ciara's album marks her most dynamic era yet, blending sultry grooves, empowering anthems, and melodic dance tracks that bridge her R&B-pop legacy with fresh production. Featuring Ecstasy, How We Roll, Wassup, and Run It Up, it's a reinvention, an unapologetic celebration of freedom, power, and personal evolution. Bold and intimate, it strengthens her connection with fans while pushing culture forward.